2022-RA-1106-ESGO Laparoscopic versus open abdominal hysterectomy in endometrial cancer patients: Analysis of outcome according to risk group. (20th October 2022) - Auletta, Valentina; Bokhua, Davit; Kather, Angela; Runnebaum, Ingo B
Abstract : Introduction/Background: For treatment of low-risk endometrial cancer, laparoscopic hysterectomy is the standard surgery approach. On the other hand, oncologic safety of minimally invasive technique in high risk disease has not yet been proven. Methodology: Between 1996 and 2010, 359 endometrial cancer patients underwent laparoscopic or abdominal hysterectomy at Jena University Hospital. Recurrence rate and survival were analysed depending on surgical approach and risk categorization by classical histopathology (low-risk: stage IA without nodes metastasis, G2 or G2 with endometroid carcinoma; high-risk: stage IB or G3 or with nodes metastasis or serous papillary or clear cell type). Median follow-up was 72 months (minimum=2, maximum=214). Results: In low risk patients, disease-free survival (DFS) rate was 95.6% and overall survival (OS) rate was 96.6% after laparoscopic hysterectomy (n=158) compared to DFS rate of 92.9% and OS rate of 100% after abdominal hysterectomy (n=43). In high risk patients, we found a DFS rate of 75.3% and OS rate of 85.1% in the laparoscopy group (n=97), while DFS rate was 73.3% and OS rate was 84.2% in the open surgery group (n=61). Proportional hazards assumption of Kaplan-Meier curves was not satisfied. Conclusion: Long-term oncologic outcome of the laparoscopic procedure was not inferior compared to open abdominal hysterectomy in both low risk and high risk endometrial carcinoma patients according to data from our cohort. Results from patients treated in our center between 2011 and 2021 are under progress.